2014
DOI: 10.17648/heringeriana.v6i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Sí­ndromes de polinização e dispersão de espécies lenhosas em um fragmento de Cerrado sentido restrito na transição Cerrado - Floresta Amazônica

Abstract: O objetivo deste estudo foi avaliar a distribuição das síndromes de polinização e dispersão entre borda e interior e entre os estratos verticais de um fragmento de cerrado sentido restrito, Ribeirão Cascalheira, Mato Grosso, Brasil. Foram estabelecidas cinco transecções de 100 x 4m, paralelas e distantes 100m entre si, onde foram medidos a altura e distância da borda de todos os indivíduos com diâmetro à altura do solo ≥ 5cm, considerando borda (primeiros 50m) e interior (últimos 50m) do fragmento. Os indivídu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
2
Order By: Relevance
“…Kinoshita et al (2005), Yamamoto et al (2006 and dos Santos et al (2009) also found that melittophilia is the most common syndrome in natural areas of the Atlantic Forest. Similar proportion have been reported from Cerrado (SILBERBAUER-GOTTSBERGER AND GOTTSBERGER, 1988), Restinga (ORMOND et al,, 1993), Caatinga (Leal et al 2006), and Amazon forest (REIS et al, 2012) environments. Thus, it appears that melittophilia is the most common pollination syndrome in practically all natural environments in Brazil.…”
Section: Resultssupporting
confidence: 83%
“…Kinoshita et al (2005), Yamamoto et al (2006 and dos Santos et al (2009) also found that melittophilia is the most common syndrome in natural areas of the Atlantic Forest. Similar proportion have been reported from Cerrado (SILBERBAUER-GOTTSBERGER AND GOTTSBERGER, 1988), Restinga (ORMOND et al,, 1993), Caatinga (Leal et al 2006), and Amazon forest (REIS et al, 2012) environments. Thus, it appears that melittophilia is the most common pollination syndrome in practically all natural environments in Brazil.…”
Section: Resultssupporting
confidence: 83%
“…A presença de animais nessa área é bastante comum principalmente às aves, sendo elas as maiores responsáveis por boa parte desse tipo de dispersão (zoocoria). Padrão de dispersão observado na área de estudo apresenta semelhança com padrões observados em outras áreas do domínio Cerrado como nos trabalhos de Reis et al (2012); Melo et al (2013). Martins et al (2008) em uma área de mata ciliar e uma área de mata de galeria localizada, respectivamente, nos municípios de Peixe e Gurupi, estado do Tocantins, na mata de galeria encontraram maior proporção de espécies zoocóricas (56%) do que anemocóricas (42%) enquanto autocoria apresentou uma proporção menor (2%), resultados semelhantes com o presente trabalho.…”
Section: Resultsunclassified
“…In a Cerrado area in the state of Tocantins, Ferreira et al (2016) found that 62.33% of the species presented zoochorous dispersion syndrome, 33.76% anemochorous, and 3.91% autochorous. Some studies about Cerrado areas show that autochorous dispersion is usually found with low frequency (Melo et al, 2013;Reis et al, 2012).…”
Section: Resultsmentioning
confidence: 99%